Supplier selection using fuzzy analytic network process - SENNAROĞLU, BAHAR (Springer Verlag, 2020)
Evaluation and selection process of suppliers has a significant impact on the effectiveness of a supply chain. Supplier selection is a multiple criteria decision making (MCDM) problem. The objective of this study is to select the best supplier among three alternatives in terms of ten decision criteria for the main raw material requirement of a company in the chemical industry. The weights of criteria and the performance values of the alternatives in terms of criteria are computed from the linguistic statements of the decision maker using five-point linguistic scale and triangular fuzzy numbers. The fuzzy analytic network process is preferred as MCDM method because of subjective uncertainty of the decision maker’s evaluations and dependence among criteria. The results provide the ranking of alternatives and selection of the best supplier. © 2020, Springer Nature Switzerland AG.
Keywords: Fuzzy analytic network process; Supplier selection; Triangular fuzzy numbers